Perancangan Typeface Mengadaptasi Are' Lancor: Identitas Kultural Madura dalam Huruf Latin - Naufan Noordyanto; Sayatman Sayatman; Nugrahardi Ramadhani (Universitas Multimedia Nusantara, 2022)
Arè' lancor, a type of sickle, is a traditional weapon and has become a Madurese cultural identity, especially in Pamekasan regency, Indonesia. Its important status in local history, folklore, and tradition, does not seem to be supported by the community with efforts to introduce Lancor through representative media to a wider audience. This research was conducted as a strategy to introduce lancor in a familiar and applicable visual language medium. The authors have conducted a typographic exploration by designing a set of typeface that contain elements of the visual character of are' lancor'. The design thinking process is used to achieve the design objectives: empathy, define, ideation, prototyping, and test/implementation. This study aims to construct knowledge about how the creative process and the stages of designing a typeface. Keywords: typography; typeface; are’ lancor; madura; cultural; promotion